Review of Clinical Pharmacokinetics of Avibactam, A Newly Approved non-β lactam β-lactamase Inhibitor Drug, In Combination Use With Ceftazidime - Giri, Poonam; Patel, Harilal; Srinivas, Nuggehally R. (Drug Research, 2019)
Avibactam, a potent non-β lactam β-lactamase inhibitor, was recently approved in the USA for combination use with ceftazidime, a cephalosporin antibiotic drug. The addition of avibactam potentiates the antimicrobial drug ceftazidime, which otherwise would have been susceptible to β-lactamases produced by variety of Gram negative pathogens. The focus of this review was to provide clinical pharmacokinetic data of avibactam to cover absorption, distribution, metabolism, and excretion aspects including any potential for avibactam to show drug-drug interactions in the clinic. Based on the review of the data, the pharmacokinetics of avibactam was generally stationary in the studied dosing regimen. The elimination half-life (approximately 1.4- 3.2 h) and volume of distribution at steady state (15.4-26.3 L) were found similar across the studies and therefore, provided the complementary pharmacokinetic attributes for combination use with ceftazidime. Renal excretion was the major pathway for the clearance of avibactam. In summary, any degree of renal dysfunction is expected to alter the pharmacokinetics of avibactam – this consideration should be factored in dosage adjustments while dosing in patients with renal impairment. Concomitant drugs that may influence renal mechanism of elimination of avibactam should be avoided and/or monitored for any impact on the pharmacokinetics of avibactam.
Keywords: Avibactam; ceftazidime; β-lactamase; pharmacokinetics; pharmacodynamics; drug-drug interaction